Covid-19 Pandemic Fatigue And Its Sociodemographic, Mental Health Status, And Perceived Causes: A Cross-sectional Study Nearing The Transition To An Endemic Phase In Malaysia - Mohd Radzniwan A Rashid; Sharifah Najwa Syed Mohamad; Ahmad Izzat Ahmad Tajjudin; Nuruliza Roslan; Aida Jaffa; Fathima Begum Syed Mohideen; Faizul Helmi Addnan; Nizam Baharom; Muslimah Ithnin (MDPI, 2024)
Scopus/ERA